The Role of Social Media in Contemporary Political Influence - Santoso, Bagus (Peneliti.net, 2024)
In today's digital era, social media has developed into a major platform that influences the political realm throughout the world. Its role in shaping public opinion and the distribution of information has changed the dynamics of political power, expanding its reach and impact on contemporary society. This study aims to analyze how social media influences politics, with a focus on political campaigns, voter participation, and information dissemination. Using content analysis and social survey methods, this research investigates the influence of political communication strategies via social media on voter behavior and public policy dynamics. The research results show that social media facilitates rapid and widespread dissemination of information, allowing politicians to reach voters at lower costs and higher efficiency compared to traditional methods. However, these platforms are also vulnerable to the spread of false information and manipulation of opinion, which can undermine the integrity of the democratic process. The study found that interactions between social media users and political content often result in polarization of opinion, which can deepen social divisions. This research underscores the importance of more effective regulations and information verification mechanisms to reduce the negative impact of social media in politics. Further research is needed to explore innovative ways of managing and utilizing social media to support more inclusive and transparent democratic processes